2021
DOI: 10.30935/cedtech/11143
|View full text |Cite
|
Sign up to set email alerts
|

Technology Integration Through Evidence-Based Multimodal Reflective Professional Training

Abstract: For technology integration to achieve intended instructional objectives, professional development is of paramount importance for in-service instructors. Technology enhanced reflection providing multimodality and evidence-based data has the potential of helping instructors achieve technology integration in their teaching. Thus, this study addressed the lack of professional development programs for in-service English language instructors aiming at technology integration through evidence-based multimodal reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The results showed that physical enjoyment and RPE do not seem to be influenced by the variability of the quality of sleep, stress, fatigue, and DOMS during SSG [ 5 ]. These results suggested that the well-being indices measured before the training sessions are used to detect the current form of players, sensitive to the identification of stress after an intense training and adapted to monitoring short-term emotional changes [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that physical enjoyment and RPE do not seem to be influenced by the variability of the quality of sleep, stress, fatigue, and DOMS during SSG [ 5 ]. These results suggested that the well-being indices measured before the training sessions are used to detect the current form of players, sensitive to the identification of stress after an intense training and adapted to monitoring short-term emotional changes [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, increasing training load (TL), an accumulation of fatigue, an imbalance between the training–recovery process, and player fitness can all influence a player’s physical, technical, tactical, and psychological reactions to a training stimulus [ 11 , 15 , 16 , 17 , 18 ]. In this regard, increased pre-fatigue states and poor recovery during training can reduce performance and induce negative psychological outcomes in participants during training sessions and competitions [ 8 , 11 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also suggested that "Reflection can be as simple as asking questions such as, 'What just happened?' [21,22]." When prompting parents to reflect on the classroom experience, we find parents genuinely excited by their observations.…”
Section: Informational and Experiential Parent Developmentmentioning
confidence: 96%
“…Using interactive techniques stimulates creative, critical and creative thinking (Hiranyachattada & Kusirirat, 2020;Kaya & Adiguzel, 2021;Lai, 2019;Mora-Luis & Martin-Gutierrez, 2020).…”
Section: Analysis Of Foreign Studiesmentioning
confidence: 99%